The Impact of Education on The Knowledge Level of PKK Woment about Cardiac Arrest in Desa Lau Dendang - Waruwu, Gertuda Tuti Wijayanti; Simanullang, Rostime Hermayerni (LLDIKTI Wilayah 1, 2024)
Introduction: Cardiac arrest is a common event that often cannot be predicted and has the potential to lead to rapid death. This condition occurs when the heart's function suddenly stops, caused by the cessation of the heart's electrical activity and accompanied by the cessation of breathing. Thus, the importance of increasing public knowledge in providing prehospital first aid, especially in recognizing the signs of cardiac arrest in adults and having the skills to perform cardiopulmonary resuscitation, has become an urgent matter. Method: this type of research is quantitative with a pre-experimental design using the one group pre-test-post-test method. The sampling technique used is Simple Random Sampling with a total of 30 respondents. Analyze the data using the Wilcoxon signed-rank test. Results: The findings of this study indicate a significant influence of education on the knowledge level of the PKK woment in Laut Dendang Village regarding cardiac arrest, with a p-value of 0.000 < 0.05. Conclusion: There is an influence of education on the knowledge level of PKK woment about cardiac arrest in Laut Dendang Village. Suggestion: It is hoped that future research will connect the existing knowledge with other factors such as sources of information, social and cultural influences, in order to enhance the quality of the research.